Nodulation of promising tropical legumes for green manuring in a phosphorus deficient soil - Chada, Sylvia de Souza (2014)
A greenhouse experiment was conducted to verify the need of Rhizobium inoculation to improve nodulation, N2 fixation and plant dry weight of 9 tropical legumes for green manuring in a phosphorus deficient Red-Yellow Podzolic soil serie Itaguaí of Rio de Janeiro State, Brazil. The following legumes species were used: Mucuna aterrima, Mucuna deeringiana, Mucuna nivea, Canavalia ensiformes, Canavalia brasiliensis, Cajanus cajan, Lablab purpureus, Crotalariajuncea and Crotalaria anagyroides. The treatments with and without inoculation did not show statistical difference for nodule number but for nodule dry weight the autochthonous strains provided higher values for C. ensiformes, M.aterrima and the weight average of all legumes. Aerial plant part dry weight and total N of aerial part showed no statistical difference for these two treatments. The application of mineral N fertilizer decreased number and dry weight of nodules and increased the aerial plant part dry weight and total N. This is an indication that maximum potential of production of those plants were not reached only with N2 fixation, demonstrating the need for the selection of more efficient Rhizobium strains for these plant species. For all parameters analised C. ensiformes showed higher values.